Innovations in Bioink Materials and 3D Bioprinting for Precision Tissue Engineering - Dwijaksara, Ni Luh Bella; Andromeda, Safrian; Rahmaning Gusti, Agrippina Waya; Siswanto, Putri Alief; Lestari Devi, Ni Luh Putu Mia; Sri Arnita, Ni Putu (Metta : Jurnal Ilmu Multidisiplin, 2024)
The progress in bioink materials and 3D bioprinting techniques has created new opportunities in tissue engineering. The goal is to develop cellular implants that closely resemble native tissues in structure, function, and microenvironment, addressing challenges such as nutrient transport and mechanical support for tissue regeneration. This literature review evaluates current trends in bioink development and 3D bioprinting methodologies, assessing their effectiveness for enhancing tissue-engineered constructs for clinical applications. Recent studies were comprehensively analyzed, focusing on novel bioink formulations, optimization of 3D bioprinting processes, and evaluate on of printed constructs' mechanical and biological properties. Various fabrication techniques and their implications for tissue integration were examined. The review shows significant progress in bioink compositions that enhance cell viability and nutrient diffusion within printed scaffolds. Constructs demonstrated improved mechanical properties and biological functionality, enabling better integration with host tissues. In vivo studies highlighted the potential of these bioprinted tissues to support cellular activity and regeneration, signifying significant advancements in clinical viability. The findings emphasize the crucial role of bioink materials and bioprinting technology in advancing tissue engineering. Continual innovation in bioink formulation and printing techniques is essential to overcome current limitations and achieve widespread clinical application. Future research should focus on personalized bioink development and expanding the range of tissues that can be effectively engineered, ultimately improving patient outcomes in regenerative medicine.